Institutional education of blind, deaf and speech-disabled children in Slovenia until World War II - Šorn, Mojca; Dobaja, Dunja (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The purpose of the following contribution may be somewhat atypical, as it deals with the so-called substitute families of the blind, visually impaired, deaf, and hearing-impaired children in Slovenia in the period between the world wars. In Slovenia, substitute families were represented by the institutes that also encompassed boarding facilities with an educational-developmental programme apart from the educationalpractical component of schooling. The expert teachers strived to ensure that as many as possible blind and deaf children could benefit from this special treatment. Based on the accessible archive materials and appropriate literature, the authors follow the path of blind and deaf children from their early years to the gaining of their professions, which guaranteed the individuals’ independence in their future life and ensured their integration into the intergenerational relations. The authors have ascertained that the blind, deaf, and speech-disabled children who were included in suitable educational and schooling processes during the first decades of the 20th century had a better chance of taking an independent part in the society. Most of them were aware that the institutes had given them excellent life lessons that transcended the mere acquisition of knowledge and physical skills.
Keywords: blind children; deaf children; speech-disabled children; education; schooling; Slovenia; 1918-1945